The Effect of the Application of BSCS 5E Instructional Design on Communication Skills and Student Learning Outcomes in Physics Subjects at SMAN 16 Batam - Welda Ningsih; Darmansyah; Zulhendri Zen; Fetri Yeni J; Emilham Mirshad; Abdul Habib Arrasyidi Desky (Postgraduate, University of Mataram, 2025)
his study aims to determine the effect of applying the BSCS 5E instructional model on students’ communication skills and learning outcomes in physics at SMAN 16 Batam. The background of this research is the low level of students’ communication skills and learning outcomes, which requires an innovative learning approach that is more active and student-centered. The study employed an experimental method with a quasi-experimental design. The subjects consisted of two classes: the experimental class using the BSCS 5E model and the control class using the TPACK model. The research instruments included a learning outcomes test and communication skills observation sheets. Data were analyzed using normality and homogeneity tests, followed by an independent t-test to examine significant differences between the two groups. The results revealed that the application of the BSCS 5E model had a significant impact on improving students’ communication skills and learning outcomes. Students in the experimental class were better able to express ideas scientifically and achieved higher learning outcomes compared to those in the control class. Therefore, the BSCS 5E instructional model proved to be effective in enhancing communication skills and learning outcomes in high school physics learning.